2016
DOI: 10.1089/rej.2015.1795
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Fraction of Huogu Formula Promotes Osteogenic Differentiation of Bone Marrow Stromal Cells Through the BMP and Wnt Signaling Pathways

Abstract: Our recent studies have shown that Huogu (HG) formula was effective both in clinic experience and in experimental osteonecrosis of the femoral head (ONFH). Given that defective of bone marrow stromal cells (MSCs) contribute to the development of osteonecrosis and MSCs show enormous potential in the treatment of ONFH, especially to aging people. How HG impacts the differentiation of MSCs and what is the underlying cellular and molecular mechanism remains largely unknown. Here, we found that an aqueous fraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Functionally, activated Wnt and BMP signaling pathways were reported to increase the ALP activity and promote the osteoblast differentiation . Similarly, the BMP and Wnt signaling pathways co‐operatively involve in the function of an aqueous fraction of Huogu, which increased ALP activity, mineralized nodules, and migration of MSCs, and further enhance osteogenesis with elevated expression of Runx2, ALP, OCN, and osterix . Together, we maintained that the activation of Wnt and BMP signaling pathways could result in the upregulation of EMX2, which promoted differentiation of MSCs into osteoblasts in MM patients.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Functionally, activated Wnt and BMP signaling pathways were reported to increase the ALP activity and promote the osteoblast differentiation . Similarly, the BMP and Wnt signaling pathways co‐operatively involve in the function of an aqueous fraction of Huogu, which increased ALP activity, mineralized nodules, and migration of MSCs, and further enhance osteogenesis with elevated expression of Runx2, ALP, OCN, and osterix . Together, we maintained that the activation of Wnt and BMP signaling pathways could result in the upregulation of EMX2, which promoted differentiation of MSCs into osteoblasts in MM patients.…”
Section: Discussionsupporting
confidence: 57%
“…A previous study has revealed that Wnt/β-catenin signaling pathway could increase BMP2 expression in osteoblasts. 40 Together, we maintained that the activation of Wnt and BMP signaling pathways could result in the upregulation of EMX2, which promoted differentiation of MSCs into osteoblasts in MM patients. F I G U R E 5 Activated Wnt signaling increased the BMP9 protein expression.…”
Section: Discussionmentioning
confidence: 55%
“…In mainland China, orthopaedic surgeons can also choose Chinese medicine as a treatment method for patients 17, 18 . Considerable experimental work has been done in this area 19–22 , and a large number of patients who received hip‐sparing therapy with integrated medicine achieved satisfactory results 23 . However, the epidemiology of ONFH has not been as thoroughly investigated as its treatment; studying its epidemiology is particulary important for a country like China with a large land area and population.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that HGF also helps improve lipoprotein metabolism [17,18]. Further experiments found that the ethyl acetate fraction of HGF helps inhibit the adipogenic differentiation of the bone marrow stromal cells [19] whereas the aqueous fraction of HGF promotes the osteogenic differentiation [20]. Here, we conducted a long-term retrospective study to evaluate the outcomes of HGF therapy for steroid-associated ONFH in convalescent SARS patients with an average of 14 years.…”
Section: Introductionmentioning
confidence: 98%